Reflections on Critical Incidents of EFL Teachers During Career Entry in Central Mexico - M. Martha Lengeling; Irasema Mora Pablo (Asociación Colombiana de Profesores de Ingles, 2016)
This article explores the reflections of critical incidents of eight beginning English as a foreign language teachers and one of their trainers in Mexico. Based upon narrative inquiry and through the use of journals, critical incidents and how they have impacted beginning teachers in their thinking were specifically looked at. From the data we found seven emerging themes which basically revolve around the relationships that are established between the teacher and the students, the emerging professional identities of the beginning teachers, and the tutor's reflection on knowledge transfer. Results showed how these teachers reflected upon their teaching practice and how the critical incidents helped them to analyze and evaluate their teaching process.